Exploring Holocene non-pollen palynomorph data from the Isle of Mull, Scottish Inner Hebrides: Ecological harmonisation and taphonomic complexity - Kevin J. Edwards; James B. Innes; J. Edward Schofield; Heather Sugden; Jeff J. Blackford (Review of Palaeobotany and Palynology, 2026)

Precise dating of the 686 ± 2 CE Newberry Pumice eruption and insights into 7th century volcanism from cryptotephra and sulfur isotopes in Greenland ice - Helen M. Innes; William Hutchison; Michael Sigl; Joseph R. McConnell; Nathan J. Chellman; Britta J.L. Jensen; Jakub T. Sliwinski; Andrea Burke (Quaternary Science Reviews, 2026)

Palynological data from Loch an t’Suidhe, Isle of Mull, Scotland - Kevin J. Edwards; Heather Sugden; James B. Innes; Jeff Blackford; J. Edward Schofield (Palynology, 2026)

Portal vein embolization versus radiation lobectomy as pre-treatment for major liver resection for colorectal liver metastases: functional assessment of the future liver remnant - Khalil Ramdhani; Rosalie C. M. van Rees; Daan Andel; Jeanine M. L. Roodhart; Arthur J. A. T. Braat; Rutger C. G. Bruijnen; Inne H. M. Borel Rinkes; Onno Kranenburg; Marnix G. E. H. Lam; Maarten L. J. Smits; Jeroen Hagendoorn (Angiogenesis, 2026)
Introduction Insufficiency of the future liver remnant (FLR) precludes surgery for liver tumors as it is associated with post-hepatectomy liver failure (PHLF). A common strategy to induce pre-operative FLR hypertrophy is portal vein embolization of the tumor bearing liver lobe. More recently, transarterial radio-embolization (radiation lobectomy, RL) has been employed. Direct functional assessment using 99mTc-mebrofenin-hepatobiliary-scintigraphy (HBS) predicts FLR sufficiency more accurately than conventional volume assessment. However, studies describing dynamic functional assessment of the FLR after RL as induction for surgery are currently lacking. This study aims to compare FLR functional changes after PVE and RL. Methods This non-interventional retrospective single-center cohort study was performed between 2016 and 2024. Patients with colorectal liver metastases (CRLM) who underwent PVE or RL because of an insufficient FLR (HBS 2 ) were included. Induction of sufficient FLR function was the primary outcome. Results Ten PVE- and ten RL-treated patients were included. The median duration to achieve sufficient FLR function was longer for RL- than PVE-treated patients (75 days (64–85) vs 31 days (28–54.5), p = 0.002). RL showed a non-significant higher median functional increase (58.6% vs 51.1%, p = 0.940) and a significantly higher voluminal increase (65.7% vs 36.8%, p = 0.049) compared to PVE. PHLF and resection margins were comparable among groups. There was no 90 day mortality. Conclusion RL represents a feasible alternative to PVE with comparable functional outcomes, particularly in patients with lower baseline FLR function or need for simultaneous tumor control. This warrants prospective studies with optimized RL protocols to better define the functional outcomes and clinical applications of RL versus PVE.

Holocene vegetation history at Wet Sleddale, Cumbria, UK, including fine-resolution pollen and non-pollen palynomorph analyses at and about the Elm Decline - James B. Innes; Samantha J. Chinn; Peter A. Ryan; Chris Orton (Vegetation History and Archaeobotany, 2026)
The vegetation history of Cumbria, in north-west England, has been intensively studied for many years by pollen analysis, particularly in the upland area of the Lake District but also the lowlands of the river Eden valley to the east and the coastal lowlands to the south and north. However, the Shap Fells, an eastern outlier of the upland massif, has so far not been the subject of palynological research despite it being an archaeologically rich area. This study presents a radiocarbon dated pollen diagram from a valley mire, covering all the Holocene except for the first and last millennia, with modelled ages throughout. Fine resolution pollen and non-pollen palynomorph (NPP) analyses are applied through the mid-Holocene Elm Decline. Results show that the site was heavily wooded in the early and mid-Holocene with tree successions similar to the rest of the Cumbrian upland, but with considerable variation in woodland composition. The site experienced only a gradual reduction in woodland cover until expansion of bog and heathland from Roman times onwards, with little human disturbance except briefly in the Bronze Age. Fine-resolution pollen analysis at the Elm Decline showed very low-scale pastoral activity at the Elm Decline and in a ‘landnam’-type phase soon afterwards, while the NPP data provided a detailed local environmental record of a wide range of wetland environments, as well as a fungal spore record that reflected a pastoral Neolithic economy. This study confirms the value of adding NPP analyses to pollen studies as they greatly improve local environmental interpretations, particularly at the fine-resolution level.

Anticipatory governance for responsible investment in energy transition minerals in the Western Congo Basin - F.A Mboringong; R.A. Riggs; J.D. Langston; A.K. Boedhihartono; D. Endamana; Y. Ge; J.L Innes; J. Lu; P. Meyfroidt; L. Weng; J. Sayer (The Extractive Industries and Society, 2025)

Ontogenetic and Geographic Phytochemical Variation in Mimulus moschatus, a Perennial Monkeyflower - Simon G. Innes; Liza M. Holeski; Nicholas J. Kooyers (Journal of Chemical Ecology, 2025)

Diverging soil peroxidase activity under ectomycorrhizal versus arbuscular mycorrhizal conifers with increasing C:N and exchangeable manganese - J. Marty Kranabetter; Freya Innes; Charlotte E. Norris; Timothy J. Philpott; Terri Lacourse; Barbara J. Hawkins (Soil Biology and Biochemistry, 2025)

Constraining the timing and climate forcing of the Long Island (Papua New Guinea) and Tarumae (Japan) eruptions and other 17th century volcanic eruptions - Imogen Gabriel; Helen M. Innes; Peter M. Abbott; Jörg Franke; Melanie Behrens; Nathan J. Chellman; Maria Hörhold; William Hutchison; Joseph R. McConnell; Birthe Twarloh; Michael Sigl (Journal of Volcanology and Geothermal Research, 2025)

A novel toolbox of GATEWAY-compatible vectors for rapid functional gene analysis in soybean composite plants - Joffrey Mejias; Alexandra Margets; Melissa Bredow; Jessica Foster; Ekkachai Khwanbua; Jackson Goshon; Thomas R. Maier; Steven A. Whitham; Roger W. Innes; Thomas J. Baum (Plant Cell Reports, 2025)

DNA metabarcoding of stomach contents shows predation impacts of black rats on island birds after a resource pulse are driven by numerical not functional response - Joanna K. Carpenter; Alexander J. F. Verry; Kieren J. Mitchell; Katherine Trought; Adrian Monks; John Innes; James Griffiths; Max Harvey; Janet M. Wilmshurst (Biological Invasions, 2025)
Generalist predator populations often surge during resource pulses but decline sharply afterwards and shift to alternative prey sources, which experience elevated predation rates. Understanding these numerical and functional responses of predators to resource pulses is especially important for effectively managing island ecosystems, where invasive mammals are generalist predators and vulnerable indigenous birds are alternative prey. We used DNA metabarcoding of stomach contents to test whether the proportion of black rats ( Rattus rattus ) consuming birds changed during and after a mast seeding year in a New Zealand beech forest. Contrary to prevailing assumptions that black rats in forests consume birds only occasionally and increase their consumption of birds once a resource pulse finishes, we found that the overall proportion of rats consuming birds was surprisingly high (19.4%), and that the proportion of rats consuming birds did not change significantly across the three years of a beech mast cycle. We detected 15 unique bird taxa in the rat stomachs and 40 unique plant taxa. The frequency of beech consumption declined across the three years, as predicted. We conclude that (1) forest birds are a common part of rat diet rather than an occasional opportunistic prey item, and (2) the impact of black rats on indigenous birds following seed pulses is predominantly driven by the numerical response (increased numbers of rats present) rather than a functional (prey switching) response. Conservation interventions that seek to maximally and consistently suppress rats are therefore likely to have the best outcomes for birds.

Can chicks smell their parents? No evidence of olfactory parent recognition in a shorebird - Marc Gilles; Sama Zefania; Tafitasoa J. Mijoro; Innes C. Cuthill; Tamás Székely; Barbara A. Caspers (Animal Behaviour, 2024)

Lateglacial Interstadial to mid-Holocene stratigraphy and palynology at Pepper Arden Bottoms, North Yorkshire, UK - James B. Innes; Mairead M. Rutherford; David R. Bridgland; Ben R. Gearey; Malcolm C. Lillie; Wishart A. Mitchell; Charlotte E. O'Brien; Richard T. Jones; Gareth J. Thompson (Proceedings of the Geologists' Association, 2024)

Detection of viable Toxoplasma gondii in retail venison - J. Thomson; M. Joeres; G. Schares; E.A. Innes; C.M. Hamilton (Food Control, 2024)

Conservation of skinks in New Zealand cities - Christopher K. Woolley; Stephen Hartley; John G. Innes; Danielle F. Shanahan; Yolanda van Heezik; Deborah J. Wilson; Nicola J. Nelson (Urban Ecosystems, 2023)
Urbanisation dramatically alters ecosystems, disrupting key processes and threatening species persistence. Despite growing knowledge of the impacts of cities on wildlife, particularly for birds and mammals, there remains a paucity of research on how urbanisation impacts other taxa, including reptiles. We examined how urbanisation affects skink communities across multiple New Zealand cities by undertaking pitfall trapping surveys in a range of habitats. Of the 20 endemic species thought to have been present historically in the cities, only four were captured during surveys, Oligosoma aeneum in Hamilton; O. polychroma , O. aeneum , and O. ornatum in Wellington; O. polychroma in Nelson; and O. aff. polychroma Clade 5 in Dunedin. Our results reveal highly variable patterns of occupancy, abundance, and complex associations with key threats and habitat modifications. Sites in Nelson and Wellington were much more likely to record skinks than Hamilton and Dunedin, and modelling showed abundance of O. polychroma was positively related to rat tracking rates when grass cover was low but showed a negative relationship when grass cover was high. O. polychroma body condition was negatively associated with the proportion of urban land cover (built up areas or transport infrastructure). The low number of captures of several species is concerning and long-term monitoring is needed to assess the trajectories of these vulnerable populations. Effective conservation management of urban wildlife requires knowledge of where populations exist and how urban processes affect persistence. For understudied urban-dwelling taxa such as reptiles, the lack of this information may be putting populations at risk.

Identification of the type locality of the South Island Brown Kiwi Apteryx australis - R. P. Scofield; J. R. Wood; L. de Nascimento; H. A. Robertson; R. M. Colbourne; V. L. De Pietri; J. Innes; J. T. Weir (Conservation Genetics, 2021)

Ocean currents and the population genetic signature of fish migrations - Nils C. Krueck; Eric A. Treml; David J. Innes; Jennifer R. Ovenden (Ecology, 2020)
Animal migrations are a fascinating and global phenomenon, yet they are often difficult to study and sometimes poorly understood. Here, we build on classic ecological theory by hypothesizing that some enigmatic spawning migrations across coastal marine habitats can be inferred from the population genetic signature of larval dispersal by ocean currents. We test this assumption by integrating spatially realistic simulations of alternative spawning migration routes, associated patterns of larval dispersal, and associated variation in the population genetic structure of eastern Australian sea mullet ( Mugil cephalus ). We then use simulation results to assess the implications of alternative spawning destinations for larval replenishment, and we contrast simulated against measured population genetic variation. Both analyses suggest that the spawning migrations of M. cephalus in eastern Australia are likely to be localized (approximately 100 km along the shore), and that spawning is likely to occur in inshore waters. Our conclusions are supported by multiple lines of evidence available through independent studies, but they challenge the more traditional assumption of a single, long‐distance migration event with subsequent offshore spawning in the East Australian Current. More generally, our study operationalizes classic theory on the relationship between fish migrations, ocean currents, and reproductive success. However, rather than confirming the traditionally assumed adaptation of migratory behavior to dominant ocean current flow, our findings support the concept of a genetically measurable link between fish migrations and local oceanographic conditions, specifically water temperature and coastal retention of larvae. We believe that future studies using similar approaches for high resolution and spatially realistic ecological–genetic scenario testing can help rapidly advance our understanding of key ecological processes in many other marine species.

Prevalence and Genetic Diversity of Toxoplasma gondii in Free-Ranging Chickens from the Caribbean - C. M. Hamilton; R. Robins; R. Thomas; C. Oura; S. Oliveira; I. Villena; E. A. Innes; F. Katzer; P. J. Kelly (Acta Parasitologica, 2019)

DArTseq molecular markers for resistance to Phytophthora cinnamomi in pineapple (Ananas comosus L.) - G. Sanewski; L. Ko; D. Innes; A. Kilian; J. Carling; J. Song (Australasian Plant Pathology, 2017)

Lateglacial and Holocene relative sea‐level changes and first evidence for the Storegga tsunami in Sutherland, Scotland - Antony J. Long; Natasha L. M. Barlow; Sue Dawson; Jon Hill; James B. Innes; Catherine Kelham; Fraser D. Milne; Alastair Dawson (Journal of Quaternary Science, 2016)
We reconstruct one of the longest relative sea‐level (RSL) records in north‐west Europe from the north coast of mainland Scotland, using data collected from three sites in Loch Eriboll (Sutherland) that we combine with other studies from the region. Following deglaciation, RSL fell from a Lateglacial highstand of +6−8 m OD (Ordnance Datum = ca. mean sea level) at ca. 15 k cal a BP to below present, then rose to an early Holocene highstand and remained at ca. +1 m OD between ca. 7 and 3 k cal a BP, before falling to present. We find no evidence for significant differential Holocene glacio‐isostatic adjustment between sites on the north‐west (Lochinver, Loch Laxford), north (Loch Eriboll) and north‐east (Wick) coast of mainland Scotland. This suggests that the region was rapidly deglaciated and there was little difference in ice loads across the region. From one site at the head of Loch Eriboll we report the most westerly sedimentary evidence for the early Holocene Storegga tsunami on the Scottish mainland. The presence of the Storegga tsunami in Loch Eriboll is predicted by a tsunami wave model, which suggests that the tsunami impacted the entire north coast of Scotland and probably also the Atlantic coastline of north‐west Scotland.

Estrogen receptor alpha promotes smoking-carcinogen-induced lung carcinogenesis via cytochrome P450 1B1 - Ming-Yue Li; Yi Liu; Li-Zhong Liu; Angel W. Y. Kong; Zhili Zhao; Bin Wu; Xiang Long; Jun Wu; Calvin S. H. Ng; Innes Y. P. Wan; Jing Du; Tony S. K. Mok; et al. (Journal of Molecular Medicine, 2015)

High frequency of copy number variations (CNVs) in the chromosome 11p15 region in patients with Beckwith–Wiedemann syndrome - Berivan Baskin; Sanaa Choufani; Yi-an Chen; Cheryl Shuman; Nicole Parkinson; Emmanuelle Lemyre; A. Micheil Innes; Dimitri J. Stavropoulos; Peter N. Ray; Rosanna Weksberg (Human Genetics, 2014)

The role of hybridization in the origin and spread of asexuality in D aphnia - Sen Xu; David J. Innes; Michael Lynch; Melania E. Cristescu (Molecular Ecology, 2013)
The molecular mechanisms leading to asexuality remain little understood despite their substantial bearing on why sexual reproduction is dominant in nature. Here, we examine the role of hybridization in the origin and spread of obligate asexuality in D aphnia pulex , arguably the best‐documented case of contagious asexuality. Obligately parthenogenetic ( OP ) clones of D. pulex have traditionally been separated into ‘hybrid’ ( Ldh SF ) and ‘nonhybrid’ ( Ldh SS ) forms because the lactase dehydrogenase ( Ldh ) locus distinguishes the cyclically parthenogenetic ( CP ) lake dwelling D aphnia pulicaria ( Ldh FF ) from its ephemeral pond dwelling sister species D . pulex ( Ldh SS ). The results of our population genetic analyses based on microsatellite loci suggest that both Ldh SS and SF OP individuals can originate from the crossing of CP female F 1 ( D . pulex × D . pulicaria ) and backcross with males from OP lineages carrying genes that suppress meiosis specifically in female offspring. In previous studies, a suite of diagnostic markers was found to be associated with OP in Ldh SS D . pulex lineages. Our association mapping supports a similar genetic mechanism for the spread of obligate parthenogenesis in Ldh SF OP individuals. Interestingly, our study shows that CP D . pulicaria carry many of the diagnostic microsatellite alleles associated with obligate parthenogenesis. We argue that the assemblage of mutations that suppress meiosis and underlie obligate parthenogenesis in D . pulex originated due to a unique historical hybridization and introgression event between D . pulex and D . pulicaria .

Comparison between open-site and below-canopy climatic conditions in Switzerland for different types of forests over 10 years (1998−2007) - V. Renaud; J. L. Innes; M. Dobbertin; M. Rebetez (Theoretical and Applied Climatology, 2011)

Collisional accretion of a Late Ordovician oceanic island arc, northern Tasman Orogenic Zone, Australia - R. A. Henderson; B. M. Innes; C. L. Fergusson; A. J. Crawford; I. W. Withnall (Australian Journal of Earth Sciences, 2011)

Successful oxytocin-assisted nipple aspiration in women at increased risk for breast cancer - Karijn P. M. Suijkerbuijk; Elsken van der Wall; Helen Meijrink; Xiaojuan Pan; Inne H. M. Borel Rinkes; Margreet G. E. M. Ausems; Paul J. van Diest (Familial Cancer, 2010)

Vegetation change during the Mesolithic and Neolithic on the Mizen Peninsula, Co. Cork, south-west Ireland - Timothy M. Mighall; Scott Timpany; Jeffery J. Blackford; Jim B. Innes; Charlotte E. O’Brien; William O’Brien; Stephan Harrison (Vegetation History and Archaeobotany, 2008)

Climate change adaptation and regional forest planning in southern Yukon, Canada - A. E. Ogden; J. L. Innes (Mitigation and Adaptation Strategies for Global Change, 2008)

Climate change adaptation and regional forest planning in southern Yukon, Canada - A. E. Ogden; J. L. Innes (Mitigation and Adaptation Strategies for Global Change, 2008)

The feasibility of administration of activated charcoal with respect to current practice guidelines in emergency department patients - Frank LoVecchio; J. Shriki; K. Innes; J. Bermudez (Journal of Medical Toxicology, 2007)

Inter-genotype variation in reproductive response to crowding among Daphnia pulex - Jay M. Fitzsimmons; David J. Innes (Hydrobiologia, 2006)

Outcomes of reciprocal invasions between genetically diverse and genetically uniform populations of Daphnia obtusa (Kurz) - N. Tagg; D. J. Innes; C. P. Doncaster (Oecologia, 2005)

Forest community analysis and the point-centered quarter method - David M. Bryant; Mark J. Ducey; James C. Innes; Thomas D. Lee; Robert T. Eckert; Daniel J. Zarin (Plant Ecology, 2005)

Genetic mating system and timing of extra-pair fertilizations in the Kentish plover - Clemens Kpper; Jnos Kis; Andrs Kosztolnyi; Tams Szkely; Innes C. Cuthill; Donald Blomqvist (Behavioral Ecology and Sociobiology, 2004)

The impacts of individual plant species on rhizosphere microbial communities in soils of different fertility - Louise Innes; Philip J. Hobbs; Richard D. Bardgett (Biology and Fertility of Soils, 2004)

Earliest Holocene vegetation history and island biogeography of the Isle of Man, British Isles - J. B. Innes; R. C. Chiverrell; J. J. Blackford; P. J. Davey; S. Gonzalez; M. M. Rutherford; P. R. Tomlinson (Journal of Biogeography, 2004)
Aim To present radiocarbon dated early Holocene pollen analytical data from two sites on the northern plain of the Isle of Man and to discuss the implications of the vegetation history in relation to severance of the island from the British Isles and to identify further evidence for divergent biogeographical development previously exemplified by the survival and apparent dwarfism of late glacial Megaloceros giganteus (Giant Deer). Location The Isle of Man, British Isles. Methods Pollen analysis and AMS radiocarbon dating of late glacial to early Holocene lake sequences at Pollies and Curragh‐y‐Cowle on the northern plain of the Isle of Man. Results The pollen data indicate a prolonged period of pre‐woodland vegetation after the late Glacial/Holocene transition, which lasted for most of the first post‐glacial millennium. This persistence of pre‐forest environments meant that the expansion of Betula woodland occurred later in this part of the Isle of Man than in adjacent areas of Britain and Ireland. Conclusions The Isle of Man, in the northern Irish Sea, was isolated from Britain during the late Glacial period perhaps explaining the delayed arrival of tree species. Delayed rise of the Holocene forest compared with surrounding regions probably reflects severance of the land‐bridge with Cumbria, but also could be a function of climate changes during the early Holocene and local environmental conditions. Late survival and the dwarfism of the Megaloceros giganteus (Giant Deer) fauna is another example of biogeographical divergence during the early Holocene/late Glacial of the Isle of Man. The delayed afforestation and absence of human hunters in the Manx early Holocene offers a permissive environmental context for the as yet unproven survival of Megaloceros into the early Holocene.

Recognition of debris flow, debris flood and flood hazard through watershed morphometrics - D. J. Wilford; M. E. Sakals; J. L. Innes; R. C. Sidle; W. A. Bergerud (Landslides, 2004)

The Role of the Fibrinolytic System in Corneal Angiogenesis - J. Mathijs Vogten; Arie Reijerkerk; Joost C.M. Meijers; Emile E. Voest; Inne H.M. Borel Rinkes; Martijn F.B.G. Gebbink (Angiogenesis, 2003)

Dating the introduction of cereal cultivation to the British Isles: early palaeoecological evidence from the Isle of Man - James B. Innes; Jeffrey J. Blackford; Peter J. Davey (Journal of Quaternary Science, 2003)
The adoption of cereal cultivation is a key benchmark in the transition from Mesolithic hunter–gatherer foraging to Neolithic farming economies, but the nature, timing and ecological–cultural context of the earliest cereal use in the British Isles and northwest Europe is still uncertain. We present AMS radiocarbon dating and fine‐resolution pollen evidence from the Isle of Man for cereal growing in the latter stages of a distinct episode of forest disturbance at almost 6000 yr BP (uncalibrated). The coherent ecological structure of this phase at the fine resolution level suggests that it records cereal cultivation well before the Ulmus decline, rather than wild grass pollen grains. This example is one of a cluster of early dates for cereal‐type pollen near the start of the sixth millenium BP, including several around the Irish Sea, which indicate that the introduction of cereal agriculture probably occurred as early in the central British Isles as in the northern European plain. This early cereal phase is followed later by a probable phase of pre‐ Ulmus decline pastoral activity. We also report Mesolithic age woodland disturbance around 7000 yr BP (uncalibrated) and the first radiocarbon dates for mid‐Holocene forest history of the Isle of Man. Copyright © 2003 John Wiley & Sons, Ltd.

Genetic variation among life-history stages of mussels in a Mytilus edulis?M . trossulus hybrid zone - J. Toro; D. J. Innes; R. J. Thompson (Marine Biology, 2003)

Reproductive isolation and reproductive output in two sympatric mussel species (Mytilus edulis, M. trossulus) and their hybrids from Newfoundland - J. E. Toro; R. J. Thompson; D. J. Innes (Marine Biology, 2002)

Observation and Confirmation of Foliar Ozone Symptoms of Native Plant Species of Switzerland and Southern Spain - J. M. Skelly; J. L. Innes; J. E. Savage; K. R. Snyder; D. Vanderheyden; J. Zhang; M. J. Sanz (Water, Air, & Soil Pollution, 1999)

Morphological variation of Mytilus edulis and Mytilus trossulus in eastern Newfoundland - D. J. Innes; J. A. Bates (Marine Biology, 1999)

A molecular approach to the ecology of a mussel ( Mytilus edulis - M. trossulus ) hybrid zone on the east coast of Newfoundland, Canada - A. S. Comesaña; J. E. Toro; D. J. Innes; R. J. Thompson (Marine Biology, 1999)

Rpg1, a soybean gene effective against races of bacterial blight, maps to a cluster of previously identified disease resistance genes - T. Ashfield; J. R. Danzer; D. Held; K. Clayton; P. Keim; M. A. Saghai Maroof; D. M. Webb; R. W. Innes (Theoretical and Applied Genetics, 1998)

Strain-specific deletions in exon 10 of rat K-kininogen and T1-kininogen genes allow mapping of both genes to rat Chromosome 11 Kngk gene AF003624 for the 421 bp fragment of the DRY Kngl1 gene. Locus names and mapping information have been submitted to the Rat Genetic Nomenclature Committee and RATMAP respectively.--> - Eugenie L. Harris; Murray R. Grigor; Brendan A. Innes; Stephen B. Harrap; George Koike; Howard J. Jacob (Mammalian Genome, 1997)

Sexual reproduction of Daphnia pulex in a temporary habitat - David J. Innes (Oecologia, 1997)